"You want to get on with the rest of your life": a qualitative study of health-related quality of life in gout. Issue 5 (May 2016) - Chandratre, Priyanka; Mallen, Christian; Roddy, Edward; Liddle, Jennifer; Richardson, Jane
Abstract The objective of the study is to examine the impact of gout and its treatments on health-related quality of life (HRQOL) using focus group interviews. From the baseline phase of a cohort study of HRQOL in gout, 17 participants (15 males, mean age 71 years) with varying attack frequency and treatment with and without allopurinol participated in one of four focus group interviews. All interviews were audio-recorded and transcribed verbatim. Data was analysed thematically. Physical and psychosocial HRQOL in gout was affected by characteristics of acute gout (particularly the unpredictable nature of attacks, location of joint involved in an attack, pain and modifications in lifestyle), lack of understanding of gout by others (association with unhealthy lifestyle, symptoms ridiculed as non-severe and non-serious) as well as participants (not considered a disease) and the lack of information provided by physicians (about causes and pharmacological as well as non-pharmacological treatments of gout). Participants emphasised the impact of acute attacks of gout and prioritised dietary modifications and treatment of acute attacks over long-term urate-lowering therapy. Characteristics of acute gout, lack of understanding and information about gout and its treatments perpetuate poor HRQOL. HRQOL (maintenance of usual diet and reduced frequency of attacks) was associated with urate-lowering treatment. Better patient, public and practitioner education about gout being a chronic condition associated with co-morbidities and poor HRQOL may improve understanding and long-term treatment of gout.